Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s11270-008-9764-2
|View full text |Cite
|
Sign up to set email alerts
|

Bromide Tolerance in Salicornia brachiata Roxb, an Obligate Halophyte

Abstract: In coastal marshy lands, halogen bromide concentration is reported to be generally higher than in the inland soils where, annual halophytic species naturally grow. The effect of bromide on plant responses is relatively less known. The objectives of this study were to assess the effect of sodium bromide (NaBr) on growth, photosynthetic pigments, tissue ions content and changes in enzymes activity in Salicornia brachiata, a salt marsh halophyte. Presence of NaBr in the root medium induced 200 percent increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In addition to commercial value of the shoots, its cultivation can also improve the soil condition as its roots promote the growth of rhizobacteria for fixing N 2 in soils with high salt (Mayak et al 2004;Jha et al 2012a, b). As the plant moderately tolerant to bromide, it can be cultivated for phytoremediation of bromide contaminated salty and marshy lands (Reddy 2009). Salicornia is a multipurpose plant with great potential for agricultural production in saline coastal areas, providing food, fodder and oil.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to commercial value of the shoots, its cultivation can also improve the soil condition as its roots promote the growth of rhizobacteria for fixing N 2 in soils with high salt (Mayak et al 2004;Jha et al 2012a, b). As the plant moderately tolerant to bromide, it can be cultivated for phytoremediation of bromide contaminated salty and marshy lands (Reddy 2009). Salicornia is a multipurpose plant with great potential for agricultural production in saline coastal areas, providing food, fodder and oil.…”
Section: Introductionmentioning
confidence: 99%
“…Bashan et al [49], found that S. bigelovii increase production (height and weight) when inoculated with some PGPB, i.e., Azospirillum halopraefrens; A. brasilense (two different strains); Vibrio aestuarianus + V. proteolyticus; Bacillus licheniformis + Phyllobacterium spp. It is worth underlining that the cultivation of Salicornia could be beneficial in order to increase soil fertility, due to the presence of rhizobacteria in its roots [50].…”
Section: Growthmentioning
confidence: 99%
“…have been grown in aquaculture systems and can be used for edible purpose [16]. Due to the presence of rhizobacteria in its roots, its cultivation is may be beneficial for increasing soil fertility and phyto-remediation of bromide [17]. Salicornia accumulates good amount of salt in its tissues, hence, it has been used to prepare vegetable salt ''Saloni'' by Council of Industrial Research-Central Salt and Marine Chemicals Research Institute (CSIR-CSMCRI), Bhavnagar, Gujarat, and recommended for high blood pressure patients due to low sodium content [18,19].…”
Section: Introductionmentioning
confidence: 99%